Effect of prefrontal cortex stimulation on regulation of amygdala response to threat in individuals with trait anxiety: a randomized clinical trial - Ironside, M; Browning, M; Ansari, T; Harvey, C; Sekyi-Djan, M; Bishop, S; Harmer, C; O'Shea, J (American Medical Association, 2018)
Importance Transcranial direct current stimulation (tDCS) of the dorsolateral prefrontal cortex (DLPFC) is under clinical investigation as a treatment for major depressive disorder. However, the mechanisms of action are unclear, and there is a lack of neuroimaging evidence, particularly among individuals with affective dysfunction. Furthermore, there is no direct causal evidence among humans that the prefrontal-amygdala circuit functions as described in animal models (ie, that increasing activity in prefrontal cortical control regions inhibits amygdala response to threat). Objective To determine whether stimulation of the prefrontal cortex reduces amygdala threat reactivity in individuals with trait anxiety. Design, Setting, and Participants This community-based randomized clinical trial used a double-blind, within-participants design (2 imaging sessions per participant). Eighteen women with high trait anxiety (age range, 18-42 years) who scored greater than 45 on the trait measure of State-Trait Anxiety Inventory were randomized to receive active or sham tDCS of the DLPFC during the first session and the other intervention during the next session. Each intervention was followed immediately by a functional imaging scan during which participants performed an attentional task requiring them to ignore threatening face distractors. Data were collected from May 7 to October 6, 2015. Main Outcomes and Measures Amygdala threat response, measured with functional magnetic resonance imaging. Results Data from 16 female participants (mean age, 23 years; range, 18-42 years), with 8 in each group, were analyzed. Compared with sham stimulation, active DLPFC stimulation significantly reduced bilateral amygdala threat reactivity (z = 3.30, P = .04) and simultaneously increased activity in cortical regions associated with attentional control (z = 3.28, P < .001). In confirmatory behavioral analyses, there was a mean improvement in task accuracy of 12.2% (95% CI, 0.30%-24.0%; mean [SD] difference in number of correct answers, 2.2 [4.5]; t15 = 1.94, P = .04) after active DLPFC stimulation. Conclusions and Relevance These results reveal a causal role for prefrontal regulation of amygdala function in attentional capture by threat in individuals with high trait anxiety. The finding that prefrontal stimulation acutely increases attentional control signals and reduces amygdala threat reactivity may indicate a neurocognitive mechanism that could contribute to tDCS treatment effects in affective disorders.